2022
DOI: 10.1371/journal.pone.0262771
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient use efficiency (NUE) of wheat (Triticum aestivum L.) as affected by NPK fertilization

Abstract: Nutrient use efficiency is crucial for increasing crop yield and quality while reducing fertilizer inputs and minimizing environmental damage. The experiments were carried out in silty clay loam soil of Lalitpur, Nepal, to examine how different amounts of nitrogen (N), phosphorus (P), and potassium (K) influenced crop performance and nutrient efficiency indices in wheat during 2019/20 and 2020/21. The field experiment comprised three factorial randomized complete block designs that were replicated three times.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 45 publications
3
21
0
Order By: Relevance
“…Their experimental results demonstrated that the combination of foliar applications of selenium and urea considerably increased all physiological parameters. Also [17] observed the similar foliar effects on the growth and physiochemical parameters in which selenium produced considerably positive impacts on the growth and physiology of plants. The conclusion of [18] about the foliar applications of selenium on brassica plants based on yield and productivity are also supporting the current findings under same environmental circumstances.…”
Section: Effect Of Urea and Selenium On The Physiological Parameters ...supporting
confidence: 55%
“…Their experimental results demonstrated that the combination of foliar applications of selenium and urea considerably increased all physiological parameters. Also [17] observed the similar foliar effects on the growth and physiochemical parameters in which selenium produced considerably positive impacts on the growth and physiology of plants. The conclusion of [18] about the foliar applications of selenium on brassica plants based on yield and productivity are also supporting the current findings under same environmental circumstances.…”
Section: Effect Of Urea and Selenium On The Physiological Parameters ...supporting
confidence: 55%
“…The lack of yield response to applied N at higher N fertilizer rates is well documented. Even in production areas without a long-standing record of excessive N fertilization (and thus, relatively low residual soil N), such as Nepal, Rawal et al (2022) reported that wheat grain yield was statistically the same for medium (125 kg ha -1 ) and high (150 kg N ha −1 ) N rates.…”
Section: Grain Yieldmentioning
confidence: 99%
“…Management practices that focus on improving plant N uptake and NUE involve irrigation methods, fertilizer input management, crop variety management in terms of water and NUE, plant N uptake management, use of controlled-release N fertilizers, use of NIs and urease inhibitors for synthetic N fertilizers, and other agronomic integrative crop management approaches ( Pan et al, 2017 ; Gweyi-Onyango et al, 2021 ; Williams et al, 2021 ; Ebbisa, 2022 ; Ma X. et al, 2022 ). Several studies regarding NUE have demonstrated that it is majorly associated with the type and method of fertilizer inputs, irrigation methods, availability of soil N, and plant N uptake ( Ye et al, 2013 ; Rawal et al, 2022 ). In modern agriculture, coupled management approach of irrigation and N management is an eco-efficient and widespread adopted technique, which can sustain rice yield under scarce water resources while ensuring environmental sustainability.…”
Section: Toward Eco-efficient N Managementmentioning
confidence: 99%